Exploring the Well-Being of Slovenian and Serbian Sport Science Students during the COVID-19 Pandemic of Summer 2022 - Brigita Banjac; Ivana M. Milovanović; Saša Pišot; Radenko M. Matić; Stevo Popović; Sandra S. Radenović; Patrik Drid (MDPI AG, 2023)
The COVID-19 pandemic profoundly changed everyday life of social actors, which inferred mental health and well-being concerns. As students of health-related studies tend to adapt better to difficult circumstances, in this study, we explored the effect of the pandemic on sports science students' well-being during the summer of 2022. The research was conducted in Slovenia and Serbia. The sample comprised n = 350 students. The PERMA-Profiler, a 15-item self-reported questionnaire, was adapted to assess well-being across five elements: positive emotions, engagement, relationships, meaning, and accomplishment. Data were collected with a questionnaire through the summer of 2022 (from May to July) and analyzed in SPSS, AMOS 26.0. The results revealed normal functioning (M = 7.72, SD ± 1.38) for the overall well-being of the students. Although all dimensions indicated high scores, relationships (M = 7.95, SD ± 1.63), meaning (M = 7.76, SD ± 1.69), and engagement (M = 7.73, SD ± 1.36) rated the highest. Furthermore, the instrument was acceptable, as the confirmatory factor analysis showed adequate reliability based on Cronbach's alpha (15 items, α = 0.94) and strong internal correlations between the PERMA dimensions. This study contributes to the previously published research, emphasizing the positive responses and successful coping of sports science students in times of complex situations, such as the COVID-19 pandemic.